PENGELUARAN KOLOSTRUM DENGAN PEMBERIAN PERAWATAN PAYUDARA DAN ENDORPHIN MASSAGE PADA IBU POST SEKSIO SESAREA - Diah Evawanna Anuhgera; Eka Fitria Panjaitan; Desika Wali Pardede; Nikmah Jalilah Ritonga; Damayanti Damayanti (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2019)
Spending colostrum in post-cesarean section mothers is difficult in the first week postpartum. Efforts to overcome colostrum disruption can use non-pharmacological methods, namely breast care and endorphin massage. This study aims to determine the expenditure of colostrum by giving breast care and endorphin massage to post-cesarean mothers. This research is a quasi-experimental study with a nonequivalent design posttest control group design. This research was carried out in the midwifery room of the second floor of Grand Medistra Lubuk Pakam Hospital during the June-July 2019 period. There were 48 participants selected using purposive sampling, with 18 assigned in breast care, endorphin massage and combination of breast care and endorphin massage. The time of spending colostrum expenditure is assessed every day while the amount of colostrum expenditure is assessed after intervening. Analysis of the data used is one-way Annova. The results showed that the combination of breast care and endorphin massage was the most effective action in the time of spending colostrum and the amount of colostrum with a value of p = 0,000. The combination of breast care and endorphin massage could be applied as an alternative therapy post-cesarean mothers.